Examining Teacher Performance from the Principals' Perceptions of Academic Supervision, Teacher Self-Efficacy, and Organizational Climate - Wiwit Rizqiani; Lia Yuliana (Journal of Pedagogy and Education Science, 2026)
This study analyzes teacher performance based on principals’ perceptions of academic supervision, teacher self-efficacy, and organizational climate, as well as their contribution to improving teacher performance through multilevel analysis. A quantitative approach with descriptive analysis was employed to support data interpretation. The study involved 111 senior high school teachers in Ngaglik District, Sleman Regency, Yogyakarta Special Region, including 15 teachers from SMA Insan Mulia Boarding School, 46 teachers from SMAN 1 Ngaglik, and 50 teachers from SMAN 2 Ngaglik. The findings indicate that principals’ academic supervision and organizational climate significantly influence teacher performance, while self-efficacy shows a weaker statistical effect. The significance values were 0.005 for academic supervision, 0.744 for self-efficacy, and 0.000 for organizational climate. Furthermore, the F-test result demonstrated a calculated F value of 19.860 with a significance level of 0.000, confirming that teacher performance is simultaneously influenced by academic supervision, self-efficacy, and organizational climate. The study concludes that both organizational and individual factors contribute to teacher performance improvement. This research is innovative because it integrates organizational climate, teacher self-efficacy, and principals’ academic supervision into a single analytical framework, emphasizing the importance of psychological and organizational dimensions in enhancing teacher performance. Teachers with stronger confidence in their professional abilities generally demonstrate better classroom management, instructional quality, and task completion. These findings highlight the importance of supportive leadership practices and positive school environments in strengthening motivation, professionalism, and performance.